2020
DOI: 10.5037/jomr.2020.11201
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Implant Placement in Non-Infected Sockets versus Infected Sockets: a Systematic Review and Meta-Analysis

Abstract: Objectives The aim of this systematic review is to compare immediate implant placement in infected extraction sockets with non-infected extraction sockets in terms of implant survival and function. Material and Methods An electronic search was conducted in PubMed, ScienceDirect, ISI Web of Knowledge and Google Scholar between January 2010 and February 2020. Studies evaluating implant survival rate and main clinical parameters were included for a qualitative and quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Such a gap leads to less crestal bone resorption and minimal midfacial soft-tissue recession. [23][24][25][26][27][28] This buccal gap even allows new bone formation, coronal to the receding buccal bone wall. [29][30][31] To achieve a minimal gap width of at least 2 mm the use of implants with a smaller diameter is advocated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a gap leads to less crestal bone resorption and minimal midfacial soft-tissue recession. [23][24][25][26][27][28] This buccal gap even allows new bone formation, coronal to the receding buccal bone wall. [29][30][31] To achieve a minimal gap width of at least 2 mm the use of implants with a smaller diameter is advocated.…”
Section: Introductionmentioning
confidence: 99%
“…To create such a gap with optimal dimensions, new insights advocate to install the implant in a more palatal position, on condition of the presence of sufficient apical bone volume. Such a gap leads to less crestal bone resorption and minimal midfacial soft‐tissue recession 23–28 . This buccal gap even allows new bone formation, coronal to the receding buccal bone wall 29–31 .…”
Section: Introductionmentioning
confidence: 99%
“…In a study by Urban et al, 44 it is indicated that smoking can be a risk factor for molar area IIP. Similarly, it is reported in the literature that despite its acceptable success rate, infectious ES needs adjunctive therapy and additional considerations if IIP is planned 39,45 . Also, it is elaborated throughout the studies that health‐related systemic conditions such as diabetes and hypertension could possibly affect the ES healing process and therefore, alter the expected outcomes 46,47 .…”
Section: Discussionmentioning
confidence: 94%
“…Presence of active periodontitis in the same sextant. Although data regarding detrimental impact of previous periodontitis on IIP is controversial 27,36,37 presence of active periodontitis within the same sextant could serve an additional risk for IIP 38,39 Evaluation of oral hygiene: poor oral hygiene may increase the failure and complications in IIP 5 …”
Section: Proposal Of a New Classification Systemmentioning
confidence: 99%
“…However, this implant procedure will result in a protracted period of tooth loss, as well as keratinization of the gums and insufficient bone mass in the edentulous area due to alveolar bone absorption following tooth extraction, which will impact the aesthetic effect of implant repair [ 3 , 4 ]. With the advances in stomatology, immediate implantation (II) technology has attracted the attention of stomatologists at home and abroad, as it not only shortens the number of surgical interventions and simplifies the treatment procedures but also preserves the soft tissue capsule to achieve the best soft tissue aesthetics [ 5 , 6 ]. However, II is not omnipotent, and it will face challenges such as inadequate wound closure and insufficient soft tissue, which will greatly compromise the aesthetics of gingival formation of the implant in the aesthetic area [ 7 ].…”
Section: Introductionmentioning
confidence: 99%